Kegiatan Pelatihan Enumerator Bagi Karyawan dan Anggota Komunitas Dapur Remaja di Depok - Diana Anggraeni; Atarieza Noorainavira Arian Putri; Sonia Amelia Ananda (Jurnal Informasi Pengabdian Masyarakat, 2024)
Service is now an important element in running a business. Good service will determine the level of satisfaction that customers give to the company. In this effort, DR. Network, a small and medium company engaged in providing internet services, seeks to determine customer satisfaction with the services provided through a survey. This research involved employees of DR. Network which is also a member of the Dapur Remaja Community which operates in the environmental sector. Training was provided because the employees involved did not understand the importance of research in supporting company performance. In addition, the employee has never conducted research. The training method provided is with knowledge of quantitative research and its procedures for two days online. The employee is then involved as an enumerator to collect customer data. The results of the training show that, by knowing and understanding the importance of research and the role of enumerators, the research process carried out runs well in accordance with the targets set by the main researcher and DR management. Network. The survey results also show that the services provided by DR. The network in certain dimensions still needs to be improved in the future.